(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article is devoted to a comprehensive analysis of the criminalization and decriminalization of domestic violence in Kazakhstan, taking into account international approaches and the role of the Ombudsman Institution. The article examines the evolution of legislation, the arguments of supporters and opponents of criminal liability, and the impact of regulatory changes on the protection of women’s rights. The data of appeals to the Office of the Ombudsman is presented, gaps in law enforcement are analyzed, and options for a national model combining the inevitability of punishment and prevention are proposed. Special attention is paid to international standards, including the Istanbul Convention, and the practices of post-Soviet and European states. The article is aimed at developing a balanced and effectively functioning mechanism to combat domestic violence.